Enfrentamento religioso espiritual por pacientes em cuidados paliativos - Lira, Cássia Celestino Barreto de (2021)
Spiritual care is an important part of health care, especially when facing the crisis of advanced diseases and at the end of life. Spiritual care is an essential domain of quality supportive and palliative care. This research aims to evaluate the influence of spirituality and / or religiosity in coping with cancer in patients under palliative care and its relationship with quality of life. It is an integrative review of the literature elaborated with the evolution of the guiding question: spirituality and religiosity influence the coping with cancer in patients under palliative care. The data were collected in databases in the month of September 2020. The terms used were: palliative care, quality of life, spirituality, religiosity. The search was designated temporarily between 2010 and 2020 and with full texts available. It was found that spirituality and / or religiosity and quality of life, mostly occurred, positive relationships with the improvement of symptoms, inner strengthening of oneself, reinvigoration of the emotional state in the hope of healing and consolidation of spiritual issues. Researching the researched studies, realizing that religious-spiritual involvement influences the lives of cancer patients in palliative care, relieving the suffering that the disease causes and being decisive for coping with stressful factors, in a continuous search to achieve well-being. Patients face disadvantages due to symptoms, especially with regard to pain and suffering, such as natural losses and feelings. The investigation of this theme was considered relevant because of its importance, which leads us to realize the value of a continuous search for what is really significant for the lives of these patients, in order to collaborate for their